COVID-19 Related Experiences Among College Students With and Without Disabilities: Psychosocial Impacts, Supports, and Virtual Learning Environments - McMaughan, Darcy Jones; Rhoads, Kelley E.; Davis, Crys; Chen, Xuewei; Han, Ho; Jones, Richard A.; Mahaffey, Carlos C.; Miller, Bridget M. (Frontiers in Public Health, 2021)
This cross-sectional analysis estimated differences, based on disability status, in college students’ (n=777) experiences during the COVID-19 pandemic. Data were modeled using t-tests and logistic regression. Most participants were white (86.2%), and women (66.4%). The mode age was 23. A third (35.6%) had at least one disability. Students reported high rates of psychosocial distress, like fear of contracting (59.7%) and spreading (74.3%) COVID-19, worry about friends and family (83.7%), and increased anxiety (72.5%), depression (59.9%), and substance use (24.7%). Forty-two percent (42.2%) were scared they would miss out on their education through virtual classes. About a third feared forgetting assignments (34.1%) and making mistakes (33.9%). Fewer students expressed apprehension about (27.9%) and intimidation by (26.3%) virtual learning. Only 17.2% would continue taking virtual classes after the pandemic. Students with disabilities (M = 12.4, SD = 4.1) experienced more psychosocial stressors compared to students without disabilities (M = 9.9, SD = 4.2), (t (775) = 7.86, p < 0.001). In adjusted models, disabled students were more than twice as likely to experience worry about medical bills (OR=2.29), loneliness (OR=2.09), and increased anxiety (OR=2.31). They were also more than three times as likely to report increased depression (OR=3.51) and changes in sexual activity (OR=3.12). However, students with disabilities (M = 1.5, SD = 1.1) also reported receiving more support compared to their non-disabled classmates (M = 1.1, SD = 1.1), (t (775) = 6.06, p < 0.001). Disabled students were more likely to feel a sense of contributing to society by following precautions (OR=1.80) and receive support from family and others (emotional support: OR=2.01, financial support: OR=2.04). Interestingly, no significant differences were found in students’ feelings associated with online or virtual learning (t (526.08) = .42, p = 0.68). Students with disabilities, though, trended toward reporting negative experiences with virtual learning. In conclusion, students with disabilities were disproportionately affected by COVID-19 stressors, but also expressed more support and a sense of contributing to the common good.